О возможных древних чешско-балтийских лексических связях - Лучиц-Федорец, Иван Иванович (Baltistica, 1989)
ABOUT THE POSSIBLE ANCIENT CZECH-BALTIC LEXICAL CONNECTIONSThe paper deals with the ancient (up to the 13th century A. D.) Czech–Baltic lexical correspondences. The West Balts are supposed to penetrate into Moravia and the territory of the middle Danube. Probably they were the Galinds, that at the turn of the two eras moved from South Prussia, their homeland, to the South and split into two branches in the territory of Volyn. According to the data of onomastics and toponymies, one of the branches settled near the Czech–Polish boundary, another moved to Podmoskovye. Here follows the enumeratien of the Czech lexemes touched upon in the paper and having the Baltic (and some of them also Russian) correspondences:Klábositi ‘to chat, to talk nonsense’, lebediti se ‘to be in bliss, luxuriate’, třměti ‘to reel’, baracht(a) ‘chatter, babble’, klopýtati‘to stumble, to stagger along’, hárati se‘to heat (about cow)’, harhule ‘growth on a tree, excrescence’, batoliti se ‘waddle’, šklebit ‘to light dimly’, kobrtati ‘to stumble’, drobiti ‘to feel feverish, to shiver’, rozblptati ‘to be boiled to pulp’, duznit ‘to bang one’s back’, obočí ‘eyebow’, duněti ‘to rattle’, žíně ‘a special rope for climbing to a beehive on a tree’, těpiti ‘to carry’, řije ‘period if heat of deers’.
Keywords: baltų - čekų ryšiai; leksika